Characterizing DNA Star-Tile-Based Nanostructures Using a Coarse-Grained Model. - Schreck, J; Romano, F; Zimmer, M; Louis, A; Doye, J (American Chemical Society, 2016)
We use oxDNA, a coarse-grained model of DNA at the nucleotide level, to simulate large nanoprisms that are composed of multi-arm star tiles, in which the size of bulge loops that have been incorporated into the tile design are used to control the flexibility of the tiles. The oxDNA model predicts equilibrium structures for several different nanoprism designs that are in excellent agreement with the experimental structures as measured by cryoTEM. In particular we reproduce the chiral twisting of the top and bottom faces of the nanoprisms as the bulge sizes in these structures are varied due to the greater flexibility of larger bulges. We are also able to follow how the properties of the star tiles evolve as the prisms are assembled. Individual star tiles are very flexible, but their structures become increasingly well-defined and rigid as they are incorporated into larger assemblies. oxDNA also finds that the experimentally observed prisms are more stable than their inverted counterparts, but interestingly this preference for the arms of the tiles to bend in a given direction only emerges after they are part of larger assemblies. These results show the potential for oxDNA to provide detailed structural insight as well as to predict the properties of DNA nanostructures, and hence to aid rational design in DNA nanotechnology.